The perspectives of South African speech- language therapists on the implementation of augmentative and alternative communication for persons with post-stroke aphasia - Tonsing, Kerstin Monika (University of Pretoria, 2022)
Mini Dissertation (M (Augmentative and Alternative Communication))--University of Pretoria, 2022.